Trauma Exposure and Mental Health Prevalence Among First Aiders - Rowe, Charlotte; Ceschi, Grazia; Boudoukha, Abdel Halim (Frontiers in Psychology, 2022)
Introduction – First aiders are commonly exposed to different forms of traumatic event (TE) during their duties such as Chronic Indirect Vicarious Exposure (CIVE) which refers to an indirect exposure to aversive details of the trauma (APA, 2013). If the psychopathological impact of TE is well documented, the mental health of first-aiders remains neglected. Therefore, our main objectives are (i) to study the link between exposure to traumatic events and psychopathological outcomes and (ii) to quantify the rates of mental health disorders amongst first aiders. Method – Our sample comprised of fifty-three volunteer first-aiders (21 females and 32 males) with an average age of 32.4 years (SD=13.6 years). Traumatic event exposure and mental health were assessed through a set of validated questionnaires completed online. Results – Rates of mental health outcomes were higher than within the general population. Females showed higher scores of PTSD than males. PTSD scores were significantly correlated with all mental issues scores, apart from tobacco use and eating disorders scores. There was a significant correlation between the number of traumatic events and the years of experience. Exposure to traumatic events only correlated with nicotine dependency. No other correlation reaches statistical significance. Discussion – The scores of all mental health outcomes were high; a surprising result, as volunteer first aiders are thought to be recruited for their strong dispositional cognitive and emotional abilities. The high levels of post-traumatic stress disorder and burnout, along with the prevalent anxiety and depression, highlight the need for greater psychosocial support. Resilience training and peer support would be useful interventions in this group.